2012
DOI: 10.3389/fnhum.2012.00230
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Dissections of Unilateral Visual Neglect Symptoms: ALE Meta-Analysis of Lesion-Symptom Mapping

Abstract: Unilateral visual neglect is commonly defined as impaired ability to attend to stimuli presented on the side of visual space contralateral to the brain lesion. However, behavioral analyses indicate that different neglect symptoms can dissociate. The neuroanatomy of the syndrome has been hotly debated. Some groups have argued that the syndrome is linked to posterior parietal cortex lesions, while others report damage within regions including the superior temporal gyrus, insula, and basal ganglia. Several recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
80
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 119 publications
(233 reference statements)
10
80
0
Order By: Relevance
“…This result with regards to distance is in keeping with earlier TMS 18 studies (Lane et al, 2013;Mahayana et al, 2014), and although rFEF has been specifically associated with egocentric processing by some (Grimsen et al, 2008), other studies have demonstrated overlapping activation in such frontal regions between egocentric and allocentric tasks (Chechlacz et al, 2012;Committeri et al,. 2004;Galati et al, 2000;Zaehle et al, 2007).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This result with regards to distance is in keeping with earlier TMS 18 studies (Lane et al, 2013;Mahayana et al, 2014), and although rFEF has been specifically associated with egocentric processing by some (Grimsen et al, 2008), other studies have demonstrated overlapping activation in such frontal regions between egocentric and allocentric tasks (Chechlacz et al, 2012;Committeri et al,. 2004;Galati et al, 2000;Zaehle et al, 2007).…”
Section: Discussionsupporting
confidence: 77%
“…There may also be a particular role for associated 5 frontal areas, including the rFEF, for egocentric space (Grimsen et al, 2008;Neggers et al, 2006;Vallar et al, 1999). However, there is also evidence for considerable overlap in the areas associated with egocentric and allocentric processing, particularly within the right frontoparietal network (Chechlacz, Rothstein, & Humpreys, 2012;Committeri et al, 2004;Galati et al, 2000;Zaehle et al, 2007).…”
Section: Introductionmentioning
confidence: 92%
“…Göbel et al, 2001;Taylor et al, 2011) and cued attention orientation paradigms (Chen et al, 2012;Heinen et al, 2011), potentially by altering goal-directed salience representations (Zenon et al, 2010). A recent meta-analysis of neuropsychological studies on neglect by Chechlacz et al (2012) furthermore revealed that damage of the AG is associated with impaired control of attention within objects. The current results suggest that the AG is also responsible for the guidance of visuospatial attention in a decision-making context.…”
Section: Discussionmentioning
confidence: 95%
“…The AG is also thought to be a key area for visuospatial attention. Lesions to the AG are associated with neglect (Chechlacz et al, 2012), and temporary disruption of AG activity by means of transcranial magnetic stimulation (TMS) affects performance on tasks requiring allocation and reorientation of visuospatial attention (reviewed in Rushworth and Taylor, 2006). Attentional processes interact with decision-making in multiple ways.…”
Section: Introductionmentioning
confidence: 99%
“…Molenberghs et al (2012; see commentary by Bartolomeo, 2012) found specific anatomical clusters for distinct neglect subtypes (e.g., personal vs. extrapersonal neglect). Chechlacz et al (2012) focuses on the dissociation between egocentric and allocentric signs of neglect. Both studies suggest that different forms of neglect are linked to both distinct and common lesion patterns involving gray and white matter.…”
mentioning
confidence: 99%